THE INFLUENCE OF SERVICE QUALITY TOWARD CUSTOMER SATISFACTION AT BIUTI HOTEL IN BANJARMASIN - Achsani, Siti Julia Normawati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
As a company that sells services, servqual is closely related to the customer satisfaction. As a company whose main role is to give service to people, Biuti Hotel needs to pay attention to the Servqual factor to satisfy their customers. This research testÂ the Servqual that given by Biuti Hotel. The purpose of this study to Analyze the influence of Service Quality toward the satisfaction of Biuti Hotel customers in Banjarmasin This research used Multiple Regression Analysis. The results of the Multiple Regression Analysis show that Servqual (tangible, reliability, responsiveness, assurance and empathy) simultaneously has an influence toward the satisfaction of Biuti Hotel customers. And when these factors are partially tested, only the variable reliability that has not significant influence toward the satisfaction of Biuti Hotel customers. The value of Adjusted R Square shows that the satisfaction of Biuti Hotel customers influenced by servequal as much as 0,807 or 80,7%. While the rest as much as 0,193 or 19,3% influenced by other variable. Key words: Servqual, Customer Satisfaction, Biuti Hotel.